Evaluation of Rare‐Earth Modified ZrB2–SiC Ablation Resistance Using an Oxyacetylene Torch. Issue 8 (26th May 2014) - Tan, Winnie; Adducci, Mitchell; Trice, Rodney; Fahrenholtz, W.
<x xml:space="preserve">Abstract</x> Rare‐earth modified ZrB2–SiC coatings were prepared via mechanical mixing Sm2O3 or Tm2O3 powders with spray‐dried ZrB2, or by chemically doping samarium ions into spray‐dried ZrB2. In either approach, SiC powders were also added and coatings were fabricated via shrouded air plasma spray. An oxyacetylene torch was utilized to evaluate the coatings under high heat flux conditions for hold times of 30 and 60 s. The resulting phases and microstructures were evaluated as a function of rare‐earth type, modification approach, and ablation time. A brittle m‐ZrO2 scale was observed in the ZrB2/SiC‐only coating after ablative tests; during cooling this scale detached from the unreacted coating. In contrast, rare‐earth modified coatings formed a protective oxide scale consisting primarily of either Sm0.2Zr0.8O1.9 or Tm0.2Zr0.8O1.9, along with small amount of m‐ZrO2. These rare‐earth oxide scales displayed high thermal stability and remained adhered to the unreacted coating during heating and cooling, offering additional oxidation protection.